Who are the citizens of the digital citizenship? - Antonio de Moraes, Joao; Benvenutti de Andrade, Eloisa [UNESP] (Int Center Information Ethics, 2015)
We live in the Digital Era, where national frontiers are vanishing. In light of cultural globalization and digital identity, a contemporary re-interpretation of classical notions like citizenship is imperative. What does it mean to be a citizen in the Digital Era? To whom can we assign digital citizenship status? In order to discuss these questions we introduce the notion of hybrid beings. Our hypothesis is that the dynamical feedback relation between the physical and digital individual's experience promotes the embodiment of a hybrid identity from which the hybrid being emerges. It is important to stress that the hybrid identities of hybrid beings are not just alter egos or avatars created in the digital world, but that they express a new dynamic around the impossibility of distinguishing between physical and digital sides of an individuals' actions. It is precisely because of a hybrid being's participation in a merged physical/digital world that we believe the notion of hybrid beings is the most suitable paradigm to exemplify the role of the digital citizen and digital citizenship.